Analisis Kemampuan Membaca Permulaan Siswa Kelas 1 SD Negeri 38 Sungai Ambawang: Penelitian - Marsela Afrianti Futri; Yunika Afryaningsih; Yuni Listiarini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Early reading skills are essential competencies that must be mastered by students from the beginning of elementary school as a foundation for academic success. However, observations at SD Negeri 38 Sungai Ambawang revealed that many first-grade students still face difficulties in reading. This study aims to analyze the early reading abilities of first-grade students based on the EGRA (Early Grade Reading Assessment) test. This research applied a descriptive qualitative approach using the EGRA test, which consists of five components: letter recognition, word reading, reading meaningless words, oral reading fluency and comprehension, and listening comprehension. The subjects were 11 first-grade students. The results showed that only 2 students were able to recognize all letters, while 3 could not recognize any letters. In word reading, 1 student read fluently, 7 read partially, and 3 could not read. In meaningless word reading, only 2 students performed well. For fluency and comprehension, 3 students answered all questions, 5 answered partially, and 3 did not answer. In listening, 2 answered all, 6 partially, and 3 did not respond. In conclusion, students’ early reading skills remain low, influenced by limited literacy stimulation, monotonous teaching, and lack of media. More varied strategies and stronger teacher–parent collaboration are needed to improve early literacy.